2003
DOI: 10.1007/s10350-004-6552-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lateral Lymph Node Micrometastases in Lower Rectal Cancer

Abstract: The presence of nodal micrometastases leads to a poor prognosis. The survival of patients with micrometastases was not different from that of patients with overt metastases. Therefore, patients with cytokeratin-positive cells in lateral lymph nodes should be regarded as having overt metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…However, the subgroup of patients with positive LLN can survive for more than five years after PSD. The reported five-year survival rates of patients with positive LLN ranged from 37.3 to 49.3 percent in each institute study, 31,32,[36][37][38][39][40] and the present study, which included a large number of patients, also showed the rate of 45.8 percent (Table 6).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…However, the subgroup of patients with positive LLN can survive for more than five years after PSD. The reported five-year survival rates of patients with positive LLN ranged from 37.3 to 49.3 percent in each institute study, 31,32,[36][37][38][39][40] and the present study, which included a large number of patients, also showed the rate of 45.8 percent (Table 6).…”
Section: Discussionsupporting
confidence: 52%
“…This could be explained by that PSD may remove micrometastasis, which is not detected by routine histopathologic examination. An immunohistochemical study by Shimoyama et al 39 revealed micrometastasis of LLN in 11 of 57 patients who had negative LLN in routine histopathologic examination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 6 studies out of 14 [14][15][16][17][18][19] micrometastasis was associated with poor prognosis compared to NND; one [26] found that it was correlated with other poor prognostic factors, and others [20][21][22][23][24][25] concluded that it did not influence patient prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, the use of immunohistochemical studies to detect otherwise undetectable micrometastases has been employed in a variety of tumor types, ranging from breast cancer to colorectal carcinoma to gastric carcinoma to pancreatic carcinoma [30][31][32][33]. It seems clear that in each organ system examined (including cervical lymph nodes in patients with head and neck carcinomas), immunohistochemical detection of micrometastases exceeds the typical resolution of conventional light microscopy alone, that is, immunohistochemistry may be expected to yield a higher detection rate of metastatic disease than routine light microscopy.…”
mentioning
confidence: 99%